Desenvolvimento e avaliação de estratégias de assistência à pilotagem para aeronaves leves - Antônio Rafael da Silva Filho (2009)
The following work presents the process of choice and development of a series of strategies to facilitate piloting on light aircrafts. These strategies are based on trajectory control instead of attitude control like it is usually done in conventional aircrafts, aiming smaller learning times as well as reduction in pilot workload, such that flight safety is increased. The complex aircraft handling mechanisms, mainly due to the atmospheric interactions and the handling coupling, turn the piloting process a difficult task which demands intense pilot training. This work aims, by the implementation of automatic control strategies to facilitatepiloting, to give the pilot the possibility to control the aircraft trajectory directly, turning it easier to pilot the airplane. The longitudinal motion will be studied and many strategies will be implemented in a flight simulator with non-linear dynamical model, developed for this matter. Users of the simulator, with different levels of knowledge on piloting, will be evaluated and their performance measured through a score system previously established. Details about the project of pilot assisting systems, including controllers tuning are presented, as the modeling andprogramming of the flight simulator. Finally, the test results are shown.